2019
DOI: 10.1002/cncr.32414
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of skeletal‐related events and mortality in men with metastatic, castration‐resistant prostate cancer: Results from the Shared Equal Access Regional Cancer Hospital (SEARCH) database

Abstract: Background Although skeletal‐related events (SREs) are linked with a reduced quality of life and worse outcomes, to the authors' knowledge the factors that predict SREs are minimally understood. The objective of the current study was to identify predictors of SREs and all‐cause mortality among men with metastatic castration‐resistant prostate cancer (mCRPC). Methods Data were collected on 837 men with bone mCRPC at 8 Veterans Affairs medical centers within the Shared Equal Access Regional Cancer Hospital (SEAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…We also investigated which patients can benefit from BHAs based on their risk of SSEs. Although other studies report elevated ALP, visceral metastases, Gleason score ≥7 and short interval between the initiation of ADT and CRPC diagnosis as risk factors, we have found that only patients with a prior SSE and with pain and/or opioid use were at higher risk of developing an SSE [33][34][35]. Patients who had either a prior SSE or pain and/or opioid use (or both) benefited the most from early BHA use.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…We also investigated which patients can benefit from BHAs based on their risk of SSEs. Although other studies report elevated ALP, visceral metastases, Gleason score ≥7 and short interval between the initiation of ADT and CRPC diagnosis as risk factors, we have found that only patients with a prior SSE and with pain and/or opioid use were at higher risk of developing an SSE [33][34][35]. Patients who had either a prior SSE or pain and/or opioid use (or both) benefited the most from early BHA use.…”
Section: Discussioncontrasting
confidence: 72%
“…In our cohort, median SSE-free survival was 12.9 months. The difference in SSE-FS in our observation can be explained by a high prevalence of SSEs compared to other studies [16,17,33,35,40]. We only included real-world patients who tend to have worse prognostic features than trial populations and thus are likely to have shorter SSE-FS.…”
Section: Discussionmentioning
confidence: 80%
“…Multiplex analysis of whole genome somatic genomic defects and outcome is needed in mPC cohorts to evaluate relative utility of specific genomic biomarkers. Pain Bone pain associated with worse OS in patients with mCRPC [70] ; more pain associated with worse OS in patients with mCRPC [71] ; achieving a pain response to treatment associated with better OS [57] ; in current study, Gleason grade pattern and time to first severe pain linked, needs to be validated Bone pain is associated with increased risk of skeletal-related events [70] . Testing pain as a specific outcome variable is indicated.…”
Section: Resultsmentioning
confidence: 94%
“…In the United States, prostate cancer is the second most common malignancy among men, with an annual incidence of approximately 250,000. 1 Although most patients with early-stage prostate cancer share a favorable prognosis, patients with metastatic castrate-resistant prostate cancer (mCRPC) frequently have poor outcomes, with a median overall survival ranging from 13 months 2 to 32 months. 3,4 Unfortunately, despite an overall decline in the incidence of prostate cancer in the United States, the incidence of metastatic prostate cancer continues to rise.…”
Section: Introductionmentioning
confidence: 99%
“…Department of Medicine, Duke University Health System, Durham, NC2 Division of Hematology-Oncology, Durham Veterans Affairs Medical Center, Durham, NC3 Raymond G. Murphy New Mexico Veterans Affairs Medical Center, Section of Hematology/Oncology, Albuquerque, NM4 National Oncology Program Office, Department of Veterans Affairs, Durham, NC5 Veterans Affairs Boston Healthcare System, Jamaica Plain Campus, Boston, MA6 Duke University Health System, Divisions of Medical Oncology, Hematology and Cell Therapeutics, Durham, NC7 Veterans Affairs Puget Sound Health Care System, Division of Hematology-Oncology, Seattle, WA…”
mentioning
confidence: 99%